Proton pump inhibitor alters Th17/Treg balance and induces gut dysbiosis suppressing contact hypersensitivity reaction in mice - Strzępa, Anna; Marcińska, Katarzyna; Kiecka, Aneta; Majewska-Szczepanik, Monika; Szczepanik, Marian (Frontiers in Immunology, 2024)
Proton pump inhibitors (PPIs), such as omeprazole, are the most commonly prescribed drugs. Treatment with PPIs alters gut microbiota composition and reduces the production of reactive oxygen (ROS) and proinflammatory IL-1β, IL-6, and TNF-α cytokines. Here, we show that omeprazole treatment suppresses the development of T cell-dependent inflammatory response using contact hypersensitivity (CHS) response, an animal model of allergic contact dermatitis (ACD), affecting up to 30% of the population. Two-week treatment with omeprazole before CHS induction, reduced inflammatory response in ears measured by ear swelling, ear biopsy weight, MPO activity, and proinflammatory cytokine production. These changes were associated with reduced frequency of TCR+ CD4+ IL-17A+ and TCR+ CD8+ IL-17A+ T cells and increased frequency of TCR+ CD4+ CD25+ FoxP3+ Treg, and TCR+ CD4+ IL-10+ Tr1 cells in peripheral lymphoid organs. Omeprazole treatment decreased the production of ROS, TNF-α, and IL-6, which supported Th17 cell induction, and increased the frequency of Clostridium cluster XIVab and Lactobacillus, implicated in Treg cell induction. The fecal microbiota transplantation (FMT) experiment confirmed the role of omeprazole-induced changes in gut microbiota profile in CHS suppression. Our data suggests that omeprazole ameliorates inflammatory response mediated by T-cells.